THE SIGNIFICANCE OF COLORECTAL CANCER IN THE MORBIDITY AND MORTALITY OF THE ADULT POPULATION OF THE SOUTH BANAT DISTRICT IN THE PERIOD FROM 2010 TO 2019 - Perovic, Aleksandra; Pavlovic Stojanovic, Jasmina; Ljiljana Lazic, Ljiljana ,; Antonijevic Djordjevic, Dragana; Bjelica, Magdalena; Popov, Ivana; Popovski, Veronika (HEALTH CARE, 2020)
Introduction/Aim: According to the GLOBOCAN data, colorectal cancer (CRC) is a major public health problem in the world, because in 2018, 1,849,518 new cases and 880,792 deaths were registered. In Serbia, CRC is the second leading cause of the occurrence of disease in men (after lung cancer), and the third in women (after breast and lung cancer). The aim of this paper is to analyze the trends of outpatient morbidity, hospitalization and death from CRC in the South Banat District in the period 2010-2019.Methods: A descriptive statistical method was used. Data from routine health statistics were analyzed for the period 2010-2019. The indicators of outpatient illness, hospital treatment and death from CRC of the adult population of the South Banat District were monitored.Results: Outpatient and inpatient morbidity rates from CRC in the South Banat District are on the rise. At the annual level, 214 patients were hospitalized in the hospitals Vršac and Pančevo due to CRC. The average age was 66.8 years and the average length of treatment was 8.4 days. Most of the hospitalized people were aged between 60 and 69. Both hospitals had a higher hospitalization rate for men than for women. About 110 people a year in the district lose their lives due to CRC, and the average age of people who died is 75.7 years. The majority of men who died were aged between 70 and 79 (32.7%), while women were aged 80 and more (31.8%). Among the leading causes of death in men, CRC is in the ninth place, while in women in the thirteenth place, and the mortality rate is higher in males.Conclusion: Due to its significant participation in the occurrence of disease and death, CRC represents a major health problem in the population of the South Banat District. In order to improve the health of the population, it is necessary to conduct organized screening for the early detection of CRC in the target population, with more intensive promotion of health and healthy lifestyles to reduce exposure to factors associated with CRC.
Keywords: colorectal cancer, morbidity, mortality, South Banat District